Social and Psychological Problems among Palestinian University Students - Hreish, Khalid; Safadi , Najwa (Dirasat: Human and Social Sciences, 2023)
Objectives: This study seeks to identify the degree of prevalence of social, academic, health, and psychological problems among Palestinian university students and to determine the differences in the level of these problems according to gender, study year, place of residence, academic specialization, and place of study. Methods: The study sample consisted of (900) respondents from four universities which are Al-Quds University, Hebron University, Birzeit University, and Al-Ahliyya Palestine University. The data were collected using a questionnaire that included (45) questions. Results: The results showed that the most common problems were health problems, where the arithmetic mean value (3.06), followed by social and psychological problems with arithmetic averages (2.94, 2.81). Also, the results indicated that there were no statistically significant differences in the level of social problems according to the variable of gender, place of residence or academic specialization. While the study revealed that there were statistically significant differences in the level of problems according to the variable of the study year in favor of the first year and the place of study in favor of Al-Quds University. Conclusions: The results emphasize the need to paying attention to the student’s physical and psychological health through conducting activities that focus on health awareness and how to deal with diseases that a student may be exposed to. Also, care should be taken to establish centers for psychological and social services in each university. Additionally, it is necessary to carry out activities aim to integrating new students into university life.